Cell‐cultivated food production and processing: A review. Issue 1 (21st April 2022) - Barzee, Tyler J.; El Mashad, Hamed M.; Cao, Lin; Chio, Allan; Pan, Zhongli; Zhang, Ruihong
Abstract: Cells cultivated in bioreactors offer many possibilities for the production of novel and nutritious food products. Scientific and technological advances in cellular agriculture and processing technologies have allowed for the development of new techniques to utilize in vitro animal cells, plant cells, and microorganisms to mimic the organoleptic and nutritional properties of traditional foods as well as to potentially develop entirely new product classes. This review compiles and discusses the state‐of‐the‐art cellular production and processing systems including 3D printing of customizable cell‐cultivated food products. In addition to the technological state‐of‐the art, this article reviews the nutritional characteristics of cell‐cultivated foods, introduces examples of new food products, and compiles economic characteristics and environmental impacts of each production system as assessed through technoeconomic analyses and lifecycle assessments. The factors influencing consumer acceptance of cell‐cultivated foods are articulated and the potential implications of these new technologies on traditional agricultural industries and food chains are discussed. Lastly, future research and development trajectories are introduced with suggestions for continued development. Abstract : Cells cultivated in bioreactors offer many possibilities for the production of novel and nutritious food products. Scientific and technological advances in cellular agriculture and processing technologies have allowed for the development of new techniques to utilize in vitro animal cells, plant cells, and microorganisms to mimic the organoleptic and nutritional properties of traditional foods as well as to potentially develop entirely new product classes. This article reviews the technological state‐of‐the‐art of cell‐cultivated foods as well as their nutritional characteristics; introduces examples of new food products; and compiles potential economic, environmental, and social impacts of new cell‐cultivated food products.